Three months of combination therapy with nano‐curcumin reduces the inflammation and lipoprotein (a) in type 2 diabetic patients with mild to moderate coronary artery disease: Evidence of a randomized, double‐blinded, placebo‐controlled clinical trial. (8th June 2022) - Dastani, Mostafa; Rahimi, Hamid Reza; Askari, Vahid Reza; Jaafari, Mahmoud Reza; Jarahi, Lida; Yadollahi, Asal; Rahimi, Vafa Baradaran
Abstract: Diabetes is one of the most common chronic diseases worldwide. Systemic inflammation (high‐sensitivity C‐reactive protein (hs‐CRP)) and lipid metabolism disruption (lipoprotein A, LipoPr (a)) play a critical role in developing and progressing atherosclerosis and acute coronary syndrome in diabetic patients. The anti‐oxidant and anti‐inflammatory effects of curcumin have been emphasized previously. Therefore, we aimed to evaluate the impact of nano‐curcumin on cardiovascular risk factors in type 2 diabetic patients with mild to moderate coronary artery disease (CAD). We performed a randomized, double‐blinded, placebo‐controlled clinical trial with type 2 diabetic patients ( n  = 64), and mild to moderate CAD (<70% stenosis in angiography). The patients received nano‐curcumin (80 mg/day) or placebo along with optimal medications for 90 days. The biofactors, including hs‐CRP and LipoPr (a), and lipid profile, were measured at the admission of patients and end of the study. Nano‐curcumin significantly mitigated the hs‐CRP and LipoPr (a) levels following 90 days of treatment ( P  < 0.001 and P  = 0.043, respectively). In addition, the mean percentage of change (%Δ) in the hs‐CRP and LipoPr (a) levels were meaningfully reduced in the nano‐curcumin group compared to the placebo group ( P  < 0.001 and P  = 0.007, respectively). Surprisingly, nano‐curcumin notably propagated the number of patients with mild (34.35%) and moderate (62.5%) hs‐CRP level category and strikingly diminished the number of patients with severe hs‐CRP level category (3.125%) compared to the placebo group ( P  = 0.016). Nano‐curcumin (80 mg/day) might prevent atherosclerosis progression and, in terms of attenuating hs‐CRP levels as an inflammation index, succedent cardiovascular events in diabetic heart patients.